Project for Strengthening the Profile of Pancasila Students: Sharing Sessions - Githa, Arum; Matahari, Tombak; Wicaksono, Ade Iva; Hasna Utami, Kharisa; Lestari, Tika Endah (Center for Research and Community Service of Sampoerna University, 2024)
The Project for Strengthening the Profile of Pancasila Students (Projek Penguatan Profil Pelajar Pancasila—P5) aims to promote the development of the Pancasila student profile through project-based learning. In today's globalization and technological advancement era, values and character education are needed to strike a balance between technological progress and human development. SMP Negeri 174 Jakarta implemented these activities for the year-8 high-school students. The community service activities began in early April 2024 and utilized a qualitative research method. This included an Internet-based literature review and discussions with resource persons. Community service activities began in early April 2024 and finished on 13 May 2024 with all completed activity. Another similar sharing session about teenagers’ well-being and mental health development must also be offered to students’ parents and teachers.